Comparison of balance and proprioception in individuals with myopia compared to healthy peers - OĞUZ, SEMRA; SARI, ZÜBEYİR (My University, 2022)
© 2022 Archives of Health Science and Research. All rights reserved.Objective: The visual system is one of the 3 most essential systems for maintaining balance. However, the evaluation of refractive error such as myopia has always been neglected in balance studies. This paper aimed to examine the differences in balance and proprioception measurements between individuals with myopia and their healthy peers. Materials and Methods: Fifteen subjects with myopic eye defects and 15 healthy peers were included in the study. Balance evaluations consisted of the tandem walk test (TWT), the limits of stability test (LOS), and the modified clinical test of sensory interaction and balance (mCTSIB). These evaluations were performed with a computer-aided NeuroCom Balance Master device. Additionally, proprioception was measured with the Biodex System 3 isokinetic dynamometer. Results: Individuals with myopic defects had higher step widths (P= .001), and end-sway (P = .007) than their healthy peers. The reaction time, maximum excursion, and directional control values of the myopia group were lower than those of the healthy peer group, but there was no difference between the results of the LOS and the m-CTSIB tests (P > .05 for all parameters). Moreover, the 60° proprioception evaluation deviation was higher in the myopia group for both dominant and non-dominant extremities. However, this deviation was not statistically significant (P > .05). Conclusion: This study showed some differences in the measured values for balance in myopic individuals compared to healthy peers. We think that the evaluation of the participants with the orthoses they use will provide more accurate results from the measurements in future studies evaluating balance and proprioception.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Sosyal ve Beşeri Bilimler; Sosyoloji; Jeofizik Mühendisliği; Mühendislik ve Teknoloji; Medicine; Health Sciences; Fundamental Medical Sciences; Social Sciences and Humanities; Sociology; Geophysical Engineering; Engineering and Technology; Klinik Tıp (MED); Temel Bilimler (SCI); Sosyal Bilimler (SOC); Klinik Tıp; Yerbilimleri; Sosyal Bilimler Genel; TIP, GENEL & DAHİLİ; JEOKİMYA VE JEOFİZİK; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Clinical Medicine (MED); Natural Sciences (SCI); Social Sciences (SOC); CLINICAL MEDICINE; GEOSCIENCES; SOCIAL SCIENCES, GENERAL; MEDICINE, GENERAL & INTERNAL; GEOCHEMISTRY & GEOPHYSICS; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Genel Yer ve Gezegen Bilimleri; Fizik Bilimleri; Genel Sağlık Meslekleri; Sağlık (sosyal bilimler); Sosyal Bilimler ve Beşeri Bilimler; Halk, Çevre ve İş Sağlığı; General Earth and Planetary Sciences; Physical Sciences; General Health Professions; Health (social science); Social Sciences & Humanities; Public Health, Environmental and Occupational Health; Balance; Myopia; Proprioception; Refractive error; Balance; myopia; proprioception; refractive error